Outcomes of therapeutic community treatment for personality disorder - Capone, Georgina; Schroder, Thomas; Clarke, Simon; Braham, Louise (Emerald, 2016)
Purpose – The purpose of this paper is to review quantitative research since 1999 evaluating the effectiveness of democratic therapeutic community (DTC) treatment for individuals with personality disorders (PD) with reference to interpersonal and offending risk outcomes.